PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STAD UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR IPA SISWA KELAS VII.2 SMP NEGERI 24 PALEMBANG - Setiogohadi . (Universitas Sriwijaya, 2014)
This research is supposed to improve student’s learning achievement in basic competence 3.4 science for students VII.2 SMP Negeri 24 Palembang with implementing of cooperative teaching model of STAD. The implementing of cooperative teaching STAD model is hoped to inject the character of cooperation among students. This reasearch is done at SMP Negeri 24 Palembang in Jalan Tegal Binangun Plaju Darat Palembang. From the research we conclude that: (1) the process of teaching by using cooperative teaching STAD type can improves the students learning activity at grade VII.2 SMP Negeri 24 Palembang. Students learning activity improved clasically from first cycle to second cycle by 16,6%. (2) the process of cooperative teaching can improves student learning achievement. STAD type learning model focus in group discussion, it means that the students who has understood the materials had to taught others students. Students learning achievement has improved clasically from first cycle to second cycle by 20%.